Analisis Dampak Pariwisata terhadap Kesehatan Lingkungan di Kawasan Wisata Bahari Pantai Ancol - Bagus Sugiarto; Johann Wahyu Hasmoro Prawiro (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This study explores the impact of tourism on environmental health in the coastal tourist area of Ancol Beach, Jakarta. As a major tourist destination in North Jakarta, Ancol Beach has experienced significant growth in visitor numbers annually. While tourism in this area provides positive contributions such as boosting the local economy and creating employment opportunities, it also poses negative environmental impacts, particularly in terms of marine pollution and increased waste accumulation during peak tourist seasons. Using a qualitative approach, this research combines in- depth interviews and field observations to analyze these issues. The results indicate that, despite adequate waste management efforts, the surge in visitors creates challenges in maintaining environmental cleanliness and marine ecosystem health. Additionally, tourists' awareness of environmental responsibility tends to decline during high-traffic periods. This study recommends enhancing waste management facilities and intensifying environmental education to support sustainable tourism management at Ancol Beach.